2010
DOI: 10.2105/ajph.2008.146423
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Adolescent Viewership and Alcohol Advertising on Cable Television

Abstract: Ad placements for beer, spirits, and alcopops increased as adolescent viewership rose from 0% to 30%, especially for female viewers. Alcohol advertising practices should be modified to limit exposure of underage viewers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…Specifically, a study using Nielsen data found advertisement placements for alcoholic beverages increased as a function of adolescent viewership [34]. Similar results have been replicated in the United Kingdom, where adolescents aged 10–15 were exposed to 51% more ready-mix drink (i.e., alcopops) alcohol advertisements than individuals aged 25 and older [26].…”
Section: Race Ethnicity Gender and Agementioning
confidence: 87%
See 1 more Smart Citation
“…Specifically, a study using Nielsen data found advertisement placements for alcoholic beverages increased as a function of adolescent viewership [34]. Similar results have been replicated in the United Kingdom, where adolescents aged 10–15 were exposed to 51% more ready-mix drink (i.e., alcopops) alcohol advertisements than individuals aged 25 and older [26].…”
Section: Race Ethnicity Gender and Agementioning
confidence: 87%
“…Underage drinkers are also exposed to alcohol advertisements more frequently than of age drinkers through myriad media [26, 3438]. Specifically, a study using Nielsen data found advertisement placements for alcoholic beverages increased as a function of adolescent viewership [34].…”
Section: Race Ethnicity Gender and Agementioning
confidence: 99%
“…For tobacco advertising, Saffer and Chaloupka (2000) report that comprehensive restrictions are needed to reduce consumption, and that limited bans will have little or no effect. Studies on self-regulation by the alcohol industry suggest that these actions have little impact on reducing exposure to alcohol advertising in youth (Chung et al, 2010;Fielder et al, 2009;Jernigan, 2009). In relation to advertising of foods HFSS, three main forms of action are most frequently put forward to limit the influence of advertising: statutory regulation, self-regulation and educational approaches.…”
Section: Solutionsmentioning
confidence: 99%
“…This study indicates that health-related advertising on US university campuses does not uniformly promote positive health practices despite evidence that environments encouraging healthy choices could make it easier for individuals to achieve and/or maintain health goals, such as a normal BMI and resist underage alcohol intake (Chung et al, 2010;Patrick et al, 2010;Reinert et al, 2005;Sallis et al, 2008). This study also indicates there are significant gaps in campus health-related policies particularly with regard to healthy eating and physical activity patterns and lack of policies covering healthrelated advertisement content.…”
Section: Discussionmentioning
confidence: 86%